ANALISIS PERHITUNGAN UPAH LEMBUR KERJA KARYAWAN PADA PT. KDC SAMARINDA - -, Rahmawati - (EKONOMIA, 2019)
PT. KDC Samarinda is in accordance with the Decree of Minister of Manpower and Transmigration of the Republic of Indonesia Number KEP.102 / MEN / VI / 2004 or not.The authors put forward the hypothesis as follows: